2014
DOI: 10.1097/jom.0000000000000116
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Combined Social and Physical Environmental Intervention on Presenteeism, Absenteeism, Work Performance, and Work Engagement in Office Employees

Abstract: Although the study showed some promising results, it is not recommended to implement the current interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 31 publications
0
62
0
5
Order By: Relevance
“…It is also worthwhile for future research to examine the links between presenteeism and affective-motivational states in the long-term, perhaps as an indication of such adjustment and/or the success of interventions. What is certain is that a more comprehensive understanding of presenteeism will enable informed interventions and perhaps address the unfortunate observations that controlled intervention studies aimed at reducing 18 presenteeism have found weak links with future health status (Christensen, Overgaard, Hansen, Søgaard, & Holtermann, 2013), that there is a lack of association between the availability of health and wellness programs and the prevalence of presenteeism (Bustillos & Trigoso, 2013) which is worrying (Capps & Harkey, 2008;Coffeng et al, 2014). Advanced research on presenteeism can help to address the limited advice currently available concerning its management and moreover to capitalise on functional presenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worthwhile for future research to examine the links between presenteeism and affective-motivational states in the long-term, perhaps as an indication of such adjustment and/or the success of interventions. What is certain is that a more comprehensive understanding of presenteeism will enable informed interventions and perhaps address the unfortunate observations that controlled intervention studies aimed at reducing 18 presenteeism have found weak links with future health status (Christensen, Overgaard, Hansen, Søgaard, & Holtermann, 2013), that there is a lack of association between the availability of health and wellness programs and the prevalence of presenteeism (Bustillos & Trigoso, 2013) which is worrying (Capps & Harkey, 2008;Coffeng et al, 2014). Advanced research on presenteeism can help to address the limited advice currently available concerning its management and moreover to capitalise on functional presenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…9 Another RCT reported a significant, but small effect only for changing the physical environment (eg, creating a coffee corner) on the absorption subscale of work engagement. 10 The last RCT found a significant effect of an online mindfulness-based intervention on Shirom's vigor scale score among workers immediately after the intervention, 11 but the effect at a longer follow-up was not assessed with an RCT design, and thus is unclear. A more effective intervention to improve work engagement needs to be developed and tested.…”
mentioning
confidence: 97%
“…4,5 There is increasing research to develop interventions to improve work engagement. We searched the literature using databases including PubMed, PsycINFO, and PsycARTICLES, and found six previous randomized controlled trials (RCTs) on this topic, [6][7][8][9][10][11] which were all published since 2012. Nevertheless, four of the six RCTs, which included lifestyle change programs such as a physical fitness, failed to show a significant improvement in work engagement 6,8 ; one focused on mindfulness-based intervention 7 and another on career management skill workshops.…”
mentioning
confidence: 99%
“…Although interventions in the social and physical work environment had no effect on sickness presenteeism, they did improve work performance 12) , and no definitive solution to this problem has been determined. It is unlikely that the causes of sickness presenteeism are limited to personal factors alone; rather, environmental factors such as marital status and housing tenure are also suspected of having a role 13) .…”
mentioning
confidence: 99%